Microstructural Design and Functional Properties of Polycrystalline Materials - Neha Sahu (International Journal of Crystalline Materials, 2025)
Polycrystalline materials, composed of an aggregate of crystallites or grains, are foundational to modern engineering applications due to their versatile functional properties. The microstructural design—encompassing grain size, shape, orientation, phase distribution, and grain boundary characteristics—plays a pivotal role in determining mechanical, thermal, electrical, and magnetic behavior. This abstract explores the intricate relationship between microstructure and functionality, emphasizing how tailored processing techniques such as thermomechanical treatments, sintering, and additive manufacturing can optimize performance. Grain boundaries, often sites of enhanced diffusion, dislocation activity, and phase segregation, significantly influence strength, ductility, corrosion resistance, and conductivity. Strategies like grain boundary engineering and texture control are employed to manipulate these interfaces for desired outcomes. For instance, ultrafine-grained metals exhibit superior strength via grain boundary strengthening, while ceramics benefit from controlled porosity and phase composition for improved thermal stability. Advanced characterization methods—such as electron backscatter diffraction (EBSD), transmission electron microscopy (TEM), and atom probe tomography—enable precise mapping of microstructural features, facilitating predictive modeling and design. Coupled with computational tools like phase-field modeling and machine learning, researchers can now simulate and optimize microstructures for targeted applications. This study underscores the importance of an integrated approach combining processing, characterization, and modeling to unlock the full potential of polycrystalline materials. Applications span aerospace, electronics, energy, and biomedical sectors, where performance demands continue to rise. Ultimately, microstructural design serves as a powerful lever to engineer materials with tailored properties, bridging the gap between fundamental science and technological innovation.
Keywords: Microstructural design; polycrystalline; sintering; thermomechanical treatments; transmission electron microscopy